Baseball in April and other stories - Soto, Gary. (San Diego : Harcourt, Inc., 2000)
A collection of eleven short stories focusing on the everyday adventures of Hispanic young people growing up in Fresno, California.
Wilson's Children.
Wilson's Junior High School.
6.0
5-8
Keywords: Mexican Americans -- California -- Fresno -- Fiction; Short stories; Mexican Americans -- Fiction; Short stories; Fresno (Calif.) -- Fiction; Fresno (Calif.) -- Fiction